Altered neuroaxonal integrity in schizophrenia and major depressive disorder assessed with neurofilament light chain in serum. (August 2021) - Bavato, Francesco; Cathomas, Flurin; Klaus, Federica; Gütter, Karoline; Barro, Christian; Maceski, Aleksandra; Seifritz, Erich; Kuhle, Jens; Kaiser, Stefan; Quednow, Boris B.
Abstract: Background: Schizophrenia (SZ) and major depressive disorders (MDD) have been frequently linked to anatomical brain alterations. However, the relationship between brain pathology, inflammation and clinical symptoms in these disorders is still unclear. Thus, by applying novel blood markers of neuroaxonal integrity such as neurofilament light chain (NfL), we can now address main issues in psychiatric research and potentially offer innovative diagnostic tools toward better clinical characterizations and monitoring in both SZ and MDD. Methods: NfL levels were measured in serum of 44 patients with SZ and in 41 patients with MDD applying single molecule array technology and compared to a healthy norm population. Main inflammatory markers (C- reactive protein, interleukins IL-6 and IL-10) were measured to define patients with inflammatory phenotype. The Digit Symbol Substitution Task (DSST) and the Letter-Number-Sequencing Task were performed to estimate cognitive function in both groups. Results: NfL levels in MDD group (but not in SZ group) were significantly higher than reference values of healthy norm population. A higher than expected proportion of patients with NfL levels above age-specific cut-off values was observed in both SZ and MDD groups. No correlation was observed between NfL and inflammatory markers. A negative correlation between DSST and NfL-values was observed in patients with MDD. Conclusions: Both SZ and MDD showed elevated serum levels of NfL, which were independent from inflammatory markers but associated with cognitive performance. Highlights: NfL is a promising blood biomarker in psychiatric disorders. NfL levels in patients with MDD are elevated and linked to cognitive performance. A high heterogeneity of NfL levels in patients with SZ is observed. NfL levels in patients with SZ and MDD are independent of peripheral inflammation.